How Australian and New Zealand schools of optometry prepare students for culturally competent practice. (19th August 2014) - Truong, Mandy; Bentley, Sharon A; Napper, Genevieve A; Guest, Daryl J; Anjou, Mitchell D
<x xml:space="preserve">Abstract</x> Background This study is an investigation of how Australian and New Zealand schools of optometry prepare students for culturally competent practice. The aims are: (1) to review how optometric courses and educators teach and prepare their students to work with culturally diverse patients; and (2) to determine the demographic characteristics of current optometric students and obtain their views on cultural diversity. Methods All Australian and New Zealand schools of optometry were invited to participate in the study. Data were collected with two surveys: a curriculum survey about the content of the optometric courses in relation to cultural competency issues and a survey for second year optometry students containing questions in relation to cultural awareness, cultural sensitivity and attitudes to cultural diversity. Results Four schools of optometry participated in the curriculum survey (Deakin University, Flinders University, University of Melbourne and University of New South Wales). Sixty‐three students (22.3 per cent) from these four schools as well as the University of Auckland participated in the student survey. Cultural competency training was reported to be included in the curriculum of some schools, to varying degrees in terms of structure, content, teaching method and hours of teaching. Among second year optometry students across Australia and New Zealand, training in cultural diversity issues was the strongest predictor of cultural awareness and sensitivity after adjusting for school, age, gender, country of birth and language other than English. Conclusion This study provides some evidence that previous cultural competency‐related training is associated with better cultural awareness and sensitivity among optometric students. The variable approaches to cultural competency training reported by the schools of optometry participating in the study suggest that there may be opportunity for further development in all schools to consider best practice training in cultural competency.